METACOGNITIVE ACTIVITIES IN GROUP DISCUSSIONS OF ELEMENTARY SCHOOL STUDENTS MATHEMATICS MULTIPLICATION MATERIAL - Dyah Triwahyuningtyas; Cholis Sadijah; Makbul Muksar; Subanji Subanji (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
Student metacognition only focuses on individuals, not yet associated with student positioning in the group. There are positioning groups whose roles change, so it is necessary to examine more deeply the characterization of students' metacognition in solving multiplication problems in group discussions in terms of student positioning. This study aims to describe students' metacognitive activities, students' roles during the discussion process, and students' metacognitive abilities related to students' roles during group discussions on multiplication material in mathematics of grade 6 students in one of the public elementary schools in Indonesia. Not only knowing the concept so that students can think critically and learn independently from students without teacher assistance, but also students must be trained in solving problems. This study used descriptive qualitative as the research method. It was found that awareness was mainly found in expert and facilitator positions, regulation was found in expert and facilitator students, and evaluation was found in all student roles. The metacognitive characteristics that emerged in group discussions were expert students as triggers (stimulus) and regulators (contribution), facilitator students as regulators (contribution) and followers (passive), and novice students as followers (passive).Metakognitif siswa hanya berfokus terhadap individu, belum dikaitkan dengan pemosisian siswa dalam kelompok. Ada kelompok pemosisian yang perannya berubah, sehingga perlu mengkaji lebih mendalam terkait karakterisasi metakognitif siswa dalam menyelesaikan masalah perkalian pada diskusi kelompok ditinjau dari pemosisian siswa. Penelitian ini bertujuan untuk mendeskripsikan aktivitas metakognitif siswa, peran siswa selama proses diskusi, dan kemampuan metakognitif siswa yang terkait dengan peran siswa selama diskusi kelompok pada materi perkalian matematika siswa kelas 6 di salah satu sekolah dasar negeri di Indonesia. Tidak hanya mengetahui konsep agar siswa dapat berpikir kritis dan belajar secara mandiri dari siswa tanpa bantuan guru, tetapi juga siswa harus dilatih dalam memecahkan masalah. Penelitian ini menggunakan deskriptif kualitatif sebagai metode penelitian. Ditemukan bahwa kesadaran terutama ditemukan pada posisi ahli dan fasilitator, regulasi ditemukan pada siswa ahli dan fasilitator, dan evaluasi ditemukan pada semua peran siswa. Karakteristik metakognitif yang muncul dalam diskusi kelompok adalah siswa ahli sebagai pemicu (stimulus) dan pengatur (kontribusi), siswa fasilitator sebagai pengatur (kontribusi) dan pengikut (pasif), dan siswa pemula sebagai pengikut (pasif).